PENGARUH GAYA KEPEMIMPINAN, DISIPLIN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN (Studi Kasus Pada PT. Karya Niaga Abadi J&T Express Jawa Timur) - Moch As'ad Rofianto; Nugroho Mardi Wibowo (Fakultas Ekonomi dan Bisnis Universita Wijaya Putra Surabaya, 2024)
This study aims to determine and analyze the effect of leadership style, organizational culture and work discipline on the performance of J & T Express employees (Study at PT Karya Niaga Abadi Surabaya). The sample in this study were 119 employees of PT Karya Niaga Abadi. Data analysis techniques performed using SPSS through Validity and reliability tests, Classical Assumption Test, multiple linear regression, F test, t test and coefficient of determination. Based on the results of statistical tests that have been carried out, it can be seen that leadership style has a significant effect on employee performance. Organizational culture has no significant effect on employee performance. Work discipline has no significant effect on employee performance. Leadership style, organizational culture, and work discipline simultaneously have a significant effect on employee performance.